TITIK TEMU ANTARA VOTING DAN SYURA DALAM PEMILIHAN PEMIMPIN DI INDONESIA PERSPEKTIF HUKUM TATA NEGARA ISLAM - Srimadona Srimadona; Sulastri Caniago (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This article discusses the position of voting and shura based on constitutional concepts in Indonesia and Islam and how the meeting point between voting and shura in the election of leaders in Indonesia from the perspective of Islamic constitutional law. Using a qualitative approach, this study finds that in a country that adheres to a democratic political system, voting is used to make very important state decisions, such as to elect representatives of the people or to elect a new leader. Voting can be done if consensus is not reached then it can be done by voting (voting). In Islam, shura means deliberation where decisions have to be made in deliberation. In Indonesia, shura is contained in the 4th principle of Pancasila which reads "The people are led by wisdom in deliberation/representation". that deliberation is a typical procedure for the Indonesian personality to formulate or decide a matter based on the will of the people. In the election of leaders, voting and shura are both used in decision making in determining a choice. Voting is actually a deliberation because before voting there is a deliberation so that the results of the decision can be approved by all members of the deliberation. Islam knows Shura and Islam also recognizes voting, the proof is that during the reign of Umar bin Khatab there was decision making through voting because there was no mutual agreement among members of the deliberation. Voting takes place in the settlement of the Sawad land case in Iraq.